Legal Reformulation of Nusyūz in Marriage From The Perspective of Critical Legal Studies - Alviani, Fitri Maulina; Nizam, Nabil (DIKTUM: Jurnal Syariah dan Hukum, 2024)
The problems of Islamic family law over time, seem increasingly complex. Included in this is nusyūz which so far has been taken for granted by society in the provisions of positive law in Indonesia. This article seeks to examine the problems of nusyūz normativity based on the critical legal studies (CLS) paradigm, namely one of the substitutions for the legal school of realism that is present in the classification of the post-modern era of law. There are two main topics of discussion: First, the ratio legis of nusyūz in Indonesian legislation from a CLS perspective; and Second, the reformulation of the upcoming nusyūz law in marriage legislation in Indonesia. This article argues that the ratio legis nusyūz in Indonesian legislation in terms of the trashing, deconstruction, and genealogy approaches of CLS still has a legal construction that is not in favor of justice and social interests as well as the reformulation of the upcoming nusyūz law in marriage legislation in Indonesia based on a philosophical, sociological, and juridical foundation can be implemented through the formation of new laws in the form of laws governing marriage law or Islamic material law or by making changes or revisions to the Compilation of Islamic Law.